Analisis Kualitas Layanan Website id.oriflame.com Terhadap Kepuasan Pelanggan Menggunakan E-S-QUAL dan E-RecS-QUAL - Rifa Izza Nurlita; Ari Kusyanti; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
id.oriflame.com website is an e-commerce of Oriflame Indonesia's beauty products that give opportunity to customers (Oriflame Consultants) to expand their business without the limited time and location. With the ease of this service, but based on the interview results, there are still a lot of complaints felt by the Consultant. It proves that the quality of the website service of id.oriflame.com has not fully satisfied the Consultant. The purpose of this study was to analyze the quality factors of id.oriflame.com website service which affect the satisfaction of Oriflame Consultant using 7 independent variables. The Data were collected through an online questionnaire of 140 respondents of Oriflame Indonesia Consultants Branch of Surabaya with the age ranges between 18-44 years. The type of this research is quantitative research that used E-S-QUAL and E-RecS-QUAL model and multiple linear regression analysis method to know the factors that influence the customers satisfaction. Based on the results of the analysis and discussion, it can be concluded that the variables that affect the customer satisfaction (Customer Satisfaction) is Efficiency, System Availability, Fulfillment, Privacy, Compensation and Contact. While the most affect of Customer Satisfaction is Fulfillment and Contact.